The infratentorial supracerebellar approach in surgery of lesions of the pineal region - Oliveira, Joana (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Surgery of pineal region lesions is considered a challenging task, due to the particular relationship of lesions in this location with neural and vascular structures. Few series with a significant experience of dealing with these patients have been reported. METHODS: We review our experience using infratentorial supracerebellar approach in the surgery of pineal region, regarding the extension of the removal, postoperative morbidity, and discussing details of the surgical technique. In all cases, a supracerebellar infratentorial approach was used in the semi sitting position. RESULTS: A total of 32 patients were operated in the past 20 years (3 germinomas, 3 teratoma, 3 pineocitoma, 2 pineal tumor of intermediate differentiation, 6 pineoblastomas, 6 low grade astrocytoma, 2 glioblastoma, 2 metastasis, 1 ependymoma, 1 epidermoid tumor, 1 cavernoma, and 2 arachnoid cyst). Total removal was achieved in 15 cases and subtotal extensive removal in 7 patients. In the remaining cases, only partial removal was possible, due to the involved pathological types. There was no surgical mortality and no cases of cerebellar venous infarction. Morbidity consisted of transient ocular movement disturbance in 14 patients, transient ataxia in 3 patients, and 1 case of local cerebrospinal fluid (CSF) fistula with meningitis that required surgical treatment. CONCLUSION: Supracerebellar infratentorial is a safe approach to lesions in the pineal region, and total or extensive subtotal removal is possible in most cases, with acceptable morbidity.